Light Sensitive Molecule for Photonic Devices - Hegde, Gurumurthy; Pearl Zynia, Fernandes; A. R., Yuvaraj; Gan, Siew Mei; Lutfor, M. R.; M. M., Yusoff (2015)
Light induced effects on rod and bent shaped liquid crystals with azobenzene moiety were investigated using UV/Vis spectrophotometer. Study revealed that shape of the structure influenced their relaxation behavior in that fast thermal back relaxation in rod shape (monoazo substitution) form, while long thermal back relaxation in bent shape forms (diazo substitution). Both relaxation times are useful for creation of optical rewritable boards, optical storage devices, etc.